Synopsis: Implications of public investments and external shocks on agriculture, economic growth and poverty in Papua New Guinea: An economywide analysis - Dorosh, Paul A.; Pradesha, Angga (International Food Policy Research Institute, 2022)
Policy simulations utilizing an economy-wide model based on PNG national accounts and survey data highlight the importance of linkages between the agricultural and non-agricultural sectors of the PNG economy. There are potentially major benefits of increased agricultural productivity for national income and urban households. To reduce rural poverty, however, transport and processing costs must be lowered, as well. Even if only half of the increase in foreign exchange earnings from the 2022 world energy price shock is absorbed into the PNG economy, the real exchange rate appreciates by 13 percent, reducing incomes from export crops. However, increased domestic demand for non-tradable crops contributes to a 10 percent income gain for the rural poor. Using a portion of increased oil and natural gas revenues to finance new investments in crop agriculture, processing and transport, provides even greater benefits by spurring real GDP growth and raising real household incomes by an additional 2 to 4 percentage points. A hypothetical carbon credit arrangement in which PNG reduces deforestation in exchange for funds used to finance cash transfers to the poorest 20 percent of both urban and rural households could raise the incomes of these groups by about 13 percent.